2006
DOI: 10.1139/f05-267
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and management of exploited shark populations based on reproductive value

Abstract: Several life history traits of sharks result in juveniles being particularly vulnerable to exploitation. However, population level impacts of harvests on juvenile sharks have not been well quantified. This paper examines a range of harvest strategies, including those targeting juveniles. Reproductive value and yield per recruit are used to compare the harvests, which are represented by Leslie matrix models with a harvest matrix. Two species are used as examples: the short-lived Rhizoprionodon taylori and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 34 publications
0
43
0
9
Order By: Relevance
“…This behaviour could explain the incidence of gravid females in the catches, as this artisanal fishery operates mainly in-shore. Gallucci et al (2006) indicated that in these fisheries the risk of collapse of shark stocks increases because a large reproductive fraction of the population is captured annually. According to the current data, the risk could be even higher because catches also include a large proportion of juveniles.…”
Section: Canis M Norrisi (Cervigón and Alcalá 1999) M Antarcticusmentioning
confidence: 99%
“…This behaviour could explain the incidence of gravid females in the catches, as this artisanal fishery operates mainly in-shore. Gallucci et al (2006) indicated that in these fisheries the risk of collapse of shark stocks increases because a large reproductive fraction of the population is captured annually. According to the current data, the risk could be even higher because catches also include a large proportion of juveniles.…”
Section: Canis M Norrisi (Cervigón and Alcalá 1999) M Antarcticusmentioning
confidence: 99%
“…The concept of the gauntlet fishery has been proposed as an effective method of harvesting long-lived species, providing that fishing mortality on adults remains extremely low (Simpfendorfer 1999;Prince 2005). Although such a harvest strategy is unlikely to provide the maximum sustainable yield (Gallucci et al 2006), it may be preferable, depending on the goals of the fishery. In an artisanal fishery, for example, the harvest of large sharks is unlikely to contribute to food security given that the flesh from these animals often contains high levels of mercury and may not be suitable for human consumption (Lyle 1984;Clarkson 1997).…”
Section: Risk Mitigation Strategies In Multispecies Tropical Shark Fmentioning
confidence: 99%
“…Elasmobranchs are an integral component of the marine ecosystem, though many populations are in decline (Gallucci et al, 2006;Camhi et al, 2009). Commercial and recreational fisheries affect the populations of the Atlantic sharpnose (Rhizoprionodon terraenovae), bonnethead (Sphyrna tiburo), and spiny dogfish sharks (Squalus acanthias; Trent et al, 1997;Rulifson, 2007).…”
Section: Introductionmentioning
confidence: 99%